The Influence of Gadgets on the Language Development of Children Aged 3-4 Years - Ilmiatul Hasanah; Widia Shofa Ilmiah (Health and Technology Journal (HTechJ), 2026)
The widespread use of screen-based media in early childhood has raised concerns regarding its potential influence on language development, particularly expressive language skills. Although digital devices may provide educational opportunities, excessive or unsupervised use may reduce verbal interaction between children and caregivers. This study aimed to examine the relationship between gadget use and expressive-language development among children aged 3–4 years. A descriptive cross-sectional mixed-methods approach was employed, integrating thematic qualitative analysis with categorical descriptive findings. Thirty children aged 3–4 years were selected using purposive sampling. Data were collected through structured observations, semi-structured interviews with parents, and assessments of children's daily gadget-use patterns. Expressive-language development was evaluated based on children's ability to answer questions appropriately, express emotions using descriptive vocabulary, and convey opinions. The findings showed that 60% of children (n = 18) demonstrated indicators of delayed expressive-language development, particularly in responding to questions and expressing personal opinions. Limited emotional vocabulary was also observed in several participants and was frequently linked by parents to prolonged gadget exposure and reduced face-to-face interaction. Conversely, some children who accessed educational content with parental guidance showed emerging language abilities, including improved vocabulary recognition. These findings suggest that while educational digital media may support early learning, excessive or unguided gadget use may limit opportunities for interactive communication, which is essential for expressive-language development. Balanced gadget use, active parental mediation, and early screening of language development are therefore critical to support optimal communication skills in early childhood.